EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PERILAKU PROKRASTINASI AKADEMIK PESERTA DIDIK KELAS XI SMK LPI SEMARANG - Nur Afnanda Dewi; Dini Rakhmawati; Farikha Wahyu Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Research on the effectiveness of group counseling services using self-management techniques to reduce the academic procrastination behavior of class The aim of this research is to determine the effectiveness of group counseling services using self-management techniques to reduce the academic procrastination behavior of class XI students at SMK LPI Semarang. This research uses quantitative research, the Pre Experimental Design method with the One Group Pretest Posttest Design model. The sample in this research was 7 students who then became the experimental group. Obtaining the population using purposive sampling technique, using self-management techniques. The data collection tool uses the academic procrastination behavior scale. The results of the hypothesis test were obtained from the paired simple t-test or t test with a significance level of ɑ = 5% (0.05) resulting in the experimental group having a sig value. (2-tailed 0.304 > 0.05) where Ha is accepted, meaning that the treatment given to the experimental group was effective. It can be concluded that group counseling services with self-management techniques are effective in reducing academic procrastination behavior.